Stimulating Self-Help Skills in Early Childhood through Natural Materials Center-Based Learning: A Qualitative Case Study - Siti Zakiyah Siswanti; Mufassirul Alam; Vongdy Xayakong (Indonesian Journal of Early Childhood Educational Research (IJECER), 2026)
The development of self-help skills is a fundamental aspect of early childhood education, as it supports children’s self-help skill, responsibility, and readiness for daily life activities. However, many early childhood learners still demonstrate limited self-help skill, indicating the need for effective and developmentally appropriate learning approaches. One promising approach is center-based learning utilizing natural materials, which provides meaningful, hands-on experiences and encourages active engagement. This study aims to explore the formation of self-help skills in children aged 4–5 years through the implementation of a natural materials center-based learning model. The study employed a qualitative case study design involving nine children as participants. Data were collected through observations, interviews, and documentation, and analyzed using pattern matching techniques to identify consistent themes and behavioral patterns. The findings revealed that children demonstrated increased self-help skills, including the ability to complete tasks independently, initiate simple problem-solving, maintain personal hygiene, and interact confidently with peers. These improvements were supported by structured and consistent scaffolding provided during center-based learning activities, which facilitated active participation and strengthened children’s confidence. In conclusion, the natural materials center-based learning model effectively promotes the development of self-help skills in early childhood by positioning teachers as facilitators who provide appropriate guidance based on children’s developmental needs. It is recommended that educators integrate natural materials and structured scaffolding strategies into center-based learning environments to optimize the development of children’s self-help skill.